Pengaruh Rebranding Logo terhadap Minat Konsumen di UMKM Warung Bu Ti di Tenggilis Mejoyo Kota Surabaya - Aqila Yusriyya Hanun; Sugito Sugito (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
Tenggilis Mejoyo is one of the sub-districts in the city of Surabaya. To advance an area, there are many things that need to be considered in handling it, such as the economy of the area. The economy in Tenggilis Mejoyo Village is built on various types of economic ladder, one of which takes part is Micro, Small and Medium Enterprises. This Micro, Small and Medium Business is not free from various problems experienced, one of the aspects that is not free from problems is the branding aspect, as observed by the Village Development Team, Tenggilis Mejoyo Village, East Java "Veteran" National Development University, namely Warung Bu Ti which sells various kinds. fried foods and kopyor ice, after conducting surveys and interviews it was discovered that this business did not have a business logo and banner as its business identity. After conducting a group discussion, the Village Development Team provided a solution to create a logo design and standing banner as an effort to advance the marketing strategy for Warung Bu Ti.